Evaluating solar and wind electricity production in the Kingdom of Bahrain to combat climate change - Alnaser, N. W.; Alnaser, W. E.; Al-Kaabi, E. A. D. (Frontiers in Built Environment, 2023)
Two large Renewable Energy (RE) systems were installed in Bahrain to examine and evaluate their performance in order to proceed further to meet Bahrain’s RE targets (10%) by 2035. Two RE sources are candidates among others, i.e., solar and wind energy. The first installation included two wind turbines, each rated at 850 kW at Awali town by the Electricity and Water Authority (EWA), and the other is a 1 MW solar PV system at Al Dur area, south of Bahrain, by a Bahrain Oil Company. A result of one year (2022) is recorded for the wind turbine, and a result of two years (2017 and 2018) for the Solar PV. The annual average produced by the first turbine in front (WT1) was found to be 899 MWh and that at the back (WT2) was 872 MWh. We found that each kW installed of wind turbines produces, annually, 1,058 kWh (Specific yield of 2.9 kWh/kW/day). It was found that a 1MW wind turbine installation in Bahrain will give an annual wind electricity of 1,057 MWh, i.e. alleviating 461 tons of CO2. The capacity factor for the wind turbines is about 12 %. Meanwhile, the annual solar electricity in year 2017 was 1,632 MWh, and in the year 2018 was 1,482 MWh. Finally, we found that the1MW solar PV will produce about 1,500 MWh annually which in turn alleviate 654 tons of CO2. In comparing this result with the wind electricity (461 tons of CO2), we conclude that a 1MW of solar PV gives more electricity than a 1 MW of wind by 42% and subsequently alleviate CO2 by 42% more than wind turbines’ installation.